2001
DOI: 10.1086/320494
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence for Black Hole Event Horizons from [ITAL]Chandra[/ITAL]

Abstract: Previously we claimed that Black Hole X-ray Novae (BHXN) in quiescence are much less luminous than equivalent Neutron Star X-ray Novae (NSXN). This claim was based on the quiescent detection of a single short period BHXN (A0620-00, P orb =7.8 hrs) and two longer period BHXN (GRO J1655-40, P orb =62.9 hrs; V404 Cyg, P orb =155.3 hrs), along with sensitive upper limits. We announce the detection of two more short period BHXN (GRO J0422+32, P orb =5.1 hrs; GS 2000+25, P orb =8.3 hrs), an upper limit for a third w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
268
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(292 citation statements)
references
References 36 publications
23
268
0
1
Order By: Relevance
“…an order of magnitude than the quiescent emission of black hole transients in similar binary systems (Garcia et al 2001), pointing to the role of the neutron star surface in producing the quiescent emission. Numerous observations during quiescent periods also revealed that there is a soft thermal component in the X-ray spectra, characterized by blackbody temperatures of 0.1 − 0.3 keV, in a fraction of sources (see Figure 6 and Table 2).…”
Section: Accreting Neutron Stars In Quiescencementioning
confidence: 94%
“…an order of magnitude than the quiescent emission of black hole transients in similar binary systems (Garcia et al 2001), pointing to the role of the neutron star surface in producing the quiescent emission. Numerous observations during quiescent periods also revealed that there is a soft thermal component in the X-ray spectra, characterized by blackbody temperatures of 0.1 − 0.3 keV, in a fraction of sources (see Figure 6 and Table 2).…”
Section: Accreting Neutron Stars In Quiescencementioning
confidence: 94%
“…Accordingly, L j;rad ¼ 0:05 ; L j;tot only accounts for the partially self-absorbed synchrotron emission from the jet. Quiescent X-ray luminosities for V404 Cyg are from Garcia et al (2001), Kong et al (2002), and Hynes et al (2004); for XTE J1118+480 from McClintock et al (2004); and for A0620À00 from Kong et al (2002) and Gallo et al (2006). large luminosity difference between A0620À00 (L X /L Edd ' 10 À8 ) and other sources whose hard-state spectra were successfully fitted by the jet model, such as XTE J1118+480 (Markoff et al 2001), GX 339À4, and Cygnus XY1 (both Markoff et al 2005), simultaneous VLA and Chandra observations of A0620À00 in quiescence have shown that the nonlinear radio/X-ray correlation for hard-state BHBs appears unbroken all the way down to 10 À8 L Edd , which argues for no substantial difference between the hard and quiescent states ; but see Xue &Cui 2007 andGallo 2007). On the other hand, recent high-statistics X-ray observations of hard-state BHBs seem to show that a geometrically thin disk is present and already extends close to the innermost stable orbit at 10 À3 L Edd (Miller et al 2006b(Miller et al , 2006aRykoff et al 2007).…”
Section: Application To A0620à00mentioning
confidence: 95%
“…Furthermore, it is claimed that a discrepancy between the quiescent luminosities of black hole and neutron star X-ray binaries provides evidence for the existence of event horizons in black holes (Garcia et al 2001). Accurate luminosity measurements are required to test this claim.…”
Section: Precise Distances and Luminositiesmentioning
confidence: 99%